PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN INOVATIF BERBASIS BAHAN SEDERHANA: TRANSFORMASI EVALUASI PEMBELAJARAN UNTUK GURU SDN 20 PANGKALPINANG - Iqbal Arrosyad, M; Nugroho, Fandi; Fhatri, Zonalisa (Jurnal Bakti untuk Negeri, 2024)
This training aims to provide knowledge and skills to teachers at SDN20 Pangkalpinang in developing innovative learning media based on simple materials and producing effective learning evaluations in the current era of technology. The methods used in this training include needs identification, training implementation, evaluation of learning outcomes, and monitoring and evaluation. Through this training, it is hoped that teachers can improve students' critical skills in Elementary School through the Feedback-Based Learning Model Based on the Socrative Application in the P5 Program. Needs identification is carried out through needs analysis and evaluation of teachers' learning evaluation practices, as an important initial step in designing a training program that meets their needs. This needs analysis provides a better understanding of the challenges faced by teachers in using innovative learning media based on simple materials and effective learning evaluation practices. The results of this training show an increase inknowledge and skills of teachers in developing innovative learning media and conducting learning evaluations. The training evaluation indicates that teachers feel more confident inimplementing new learning strategies and using technology in learning. Further monitoring and evaluation are needed to ensure the sustainability of implementing new learning strategies and the use of technology in learning.